Ìyàmi: símbolo ancestral feminino no Brasil - Azevedo, Vanda Alves Torres (2006)
Ìyàmi, primordial mother, deity of practical the religious Afro-Brazilians in its originary symbol, are our object of study. Ìyàmi is basic in the cults of African origin. To study and to investigate the real knowledge on the conception of ìyàmi, its venerability,its influence in the practical one of the cult to òrìsàs, as well as its symbols, its celebration, its prayers and its praises are our objectives. To rescue the identity of Ìyàmi is arduous task, therefore it implies in the overcoming of the preconception and the duturpation reductia vision that if made on the feminine ancestral aspect. Ìyàmi ancestral mother, mythical deity,collective representation of the feminine ancestral genitor entities, deity of practical the religious Afro-Brazilians. Ìyàmi came to Brazil with descendants of populations of Africa Occidental person, primordial, matrix first of which begin all the creation of the material world